God, Evil, and Meticulous Providence - Reichenbach, Bruce R. (Religions, 2022)
James Sterba has constructed a powerful argument for there being a conflict between the presence of evil in the world and the existence of God. I contend that Sterba’s argument depends on a crucial assumption, namely, that God has an obligation to act according to the principle of meticulous providence. I suggest that two of his analogies confirm his dependence on this requirement. Of course, his argument does not rest on either of these analogies, but they are illustrative of the role that meticulous providence plays in his argument. I then investigate the ethical principles Sterba invokes in his use of meticulous providence and suggest that not only do we often not predicate goodness of human persons based on these principles of obligation, but that these principles are much too stringent to function to determine moral obligations and moral goodness. From there, I contend that to think that God has a similar obligation regarding meticulous providence in order to be good encounters several serious problems, especially with respect to the soul-building Sterba wants to preserve. I conclude by considering Sterba’s reply in terms of a limited application of meticulous providence.